(untitled) (Journal of Partial Differential Equations, 2020)
The existence of the attractors of the periodic initial value problem for the Landau-Lifshitz-Maxwell equations in one and two space dimensions is proved. We also get accurate estimates of the upper bounds of Hausdorff and fractal dimensions for the attractors by means of uniform a priori estimates for time and Lyapunov functional method.